ISSUES OF DEVELOPMENT OF STUDENTS' INDEPENDENT LEARNING COMPETENCE IN THE CONDITIONS OF DIGITALIZATION OF EDUCATION (Scientific journal of the Fergana State University, 2024)
This article describes the content and essence of the concepts of independent education, independent work, independent work of students. Also, in the conditions of digitization of education, the issues of developing students' independent learning competence were discussed, and the problems that may arise in the process of imparting knowledge to students were discussed. In the conditions of current digitization, increasing the share of independent education hours, students' independent education, critical and creative thinking, systematic analysis, and formation of entrepreneurial skills are seen as the main tasks of the day. It has been shown that the need to develop independent education competencies by directing the educational process of students to the formation of practical skills is one of the requirements of the present time. In this regard, it is necessary to widely introduce advanced pedagogical technologies, educational programs and teaching-methodical materials based on international educational standards into the educational process, and opinions on this are presented. Currently, as all state higher education institutions in Uzbekistan have switched to the credit-module system, the hours allocated to independent education in the subjects of the curricula of all educational directions and specialties make up 50-60 percent of the total hours. As an example, the primary education course is selected and the hours of subjects are explained.